Project risk management: A deterministic quantitative technique for assessment and mitigation. Issue 3 (April 2017) - Muriana, Cinzia; Vizzini, Giovanni
Abstract: The paper presents a deterministic technique for assessing and preventing project risks, by determining the risk of the Work Progress Status. Firstly, the performance of the input factors, namely the costs, quality, and time, are detected, that reflect the Iron Triangle of the Project Management. As each phase ends, the actual values of the input factors are detected and compared with that planned, and corrective actions are taken for considering the impact of the actual performances on the overall project. Thus, the current risk degree of the project is determined through the Weighted Sum Method. If it is higher than planned, preventive actions are taken, in order to mitigate the risk of the entire project. Practical applications of the technique relate to routine projects and those cases in which the schedule/costs/requirements are to be defined in the planning phase, and deviations are detected in the progress phase. Highlights: Project risk is of fundamental importance in assessing the performances. Quantitative risk assessment and management allows for fast decision-making. Work Progress deviations from planned values impact on project risk profile The risk index of Work Progress Status allows us to determine the risk of the project. Corrective/preventive actions based on risk index balance the risk among WPSs